STEM-05. FUNCTIONAL MAPPING REVEALS WIDESPREAD REMODELLING AND UNRECOGNIZED PATHWAY DEPENDENCIES IN RECURRENT GLIOBLASTOMA. (12th November 2021) - Chokshi, Chirayu R; Tieu, David; Brown, Kevin R; Venugopal, Chitra; Liu, Lina; Kuhlmann, Laura; Rossotti, Martin A; Chan, Katherine; Tong, Amy H Y; Savage, Neil; McKenna, Dillon; Aghaei, Nikoo; et al.
Abstract: Resistance to genotoxic therapies and tumor recurrence are hallmarks of glioblastoma (GBM), an aggressive brain tumor. Here, we explore the functional drivers of post-treatment recurrent GBM. By conducting genome-wide CRISPR-Cas9 screens in patient-derived GBM models, we uncover distinct genetic dependencies in recurrent tumor cells that were absent in their patient-matched primary predecessors, accompanied by increased mutational burden and differential transcript and protein expression. These analyses support parallel tumor-intrinsic mechanisms of treatment resistance which rely on acquisition of immunosuppressive capacity, including a defective mismatch repair pathway, ablation of PTEN activity, and a novel combination of de novo mutations in SWI/SNF components. We map a multilayered genetic and functional response to resist chemoradiotherapy and drive tumor recurrence, identifying protein tyrosine phosphatase 4A2 ( PTP4A2 ) as a novel driver of self-renewal, proliferation and tumorigenicity at GBM recurrence. Mechanistically, genetic perturbation and a small molecule inhibitor of PTP4A2 repress axon guidance activity through a dephosphorylation axis with roundabout guidance receptor 1 (ROBO1) and exploit a genetic dependency on ROBO signaling. Importantly, engineered anti-ROBO1 single-domain antibodies also mimic the effects of PTP4A2 inhibition. We conclude that functional reprogramming drives tumorigenicity and present a dependence on a PTP4A2-ROBO1 signaling axis at GBM recurrence.